Elaborasi Filosofis Terhadap Perbedaan Tafsir Mitos Ogoh-Ogoh Di Media Sosial - Sugiharta, I Putu Suweka Oka; Yudhasatya Dharma, I Wayan; Ulio (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2026)
Ogoh-ogoh represents a symbol of the neutralization of negative potentials inherent in space and time (Bhuta Kala). These spatial and temporal aspects are vulnerable to imbalance, whether occurring naturally or caused by human activities. On a mythological level, Bhuta Kala is manifested as terrifying beings, symbolizing the adverse consequences arising from the disruption of spatial and temporal harmony. There are two ways through which humans confront the negative potentials of space and time. First, by avoiding mistakes that lead to environmental damage or disharmony. When this effort proves ineffective, humans resort to the second approach, namely surrendering themselves to the omnipotence of God. Through total surrender, humans come to realize their true nature as spiritual beings rather than material entities. Within the Nyepi ritual sequence, which is closely associated with the presence of ogoh-ogoh, efforts to prevent negative forces and acts of self-surrender that awaken essential awareness continuously take place. The commitment of Balinese Hindus to preserving the sacredness of ogoh-ogoh stems from the profound value of the meanings embodied within it. Although ogoh-ogoh is a product of relatively recent creative expression, some groups oppose its profane interpretation. Differences in the interpretation of the ogoh-ogoh myth have become increasingly widespread along with the growth of social media. This study employs a qualitative descriptive method using a literature review and discourse analysis of social media content that presents differing interpretations of the ogoh-ogoh myth. The article aims to philosophically elaborate the variations in interpretations of the ogoh-ogoh myth circulating on social media by examining their ontological, epistemological, and axiological aspects. The findings reveal that ogoh-ogoh, as a form of cultural expression, is highly susceptible to commodification, resulting in a shift from the sacred to the profane dimension. Social media plays a dual role, both intensifying interpretative differences and serving as a medium for disseminating its authentic meaning. Achieving an appropriate understanding of ogoh-ogoh requires philosophical elements that foster vigilance against misinterpretation while reinforcing a holistic comprehension.